2021
DOI: 10.5708/ejmh.16.2021.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Loneliness among Older Adults in South-Eastern Nigeria : Implications for Social Workers

Abstract: Old-age loneliness is a crucial public health issue with mortality consequences as well as other negative health conditions and lifestyles including depression, substance abuse, sedentary lifestyles, and suicide ideation. This study investigated the predictors of loneliness among older adults in Nigeria’s southeast in order to articulate some interventions that will plummet the issue. A structured questionnaire (N = 516), in-depth interviews (N = 8), and focus group discussion (N = 16) were used to collect dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
15
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 39 publications
1
15
0
Order By: Relevance
“… Roos et al (2019) did not provide the qualitative study design but reported that a critical-realist ontology underpins their study. The two mixed-method studies did not state their specific design ( Ebimgbo et al, 2021 ; Nzabona et al, 2016 ).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“… Roos et al (2019) did not provide the qualitative study design but reported that a critical-realist ontology underpins their study. The two mixed-method studies did not state their specific design ( Ebimgbo et al, 2021 ; Nzabona et al, 2016 ).…”
Section: Resultsmentioning
confidence: 99%
“…Among the 21 quantitative and mixed-method studies, 12 (57%) studies used original or modified UCLA in assessing loneliness ( Abedini et al, 2020 ; Cacioppo et al, 2017 ; Ebimgbo et al, 2021 ; Gonyea et al, 2018 ; Hawkley & Kocherginsky, 2018 ; Igbokwe et al, 2020 ; Mannes et al, 2016 ; Ntozini & Abdullahi, 2021 ; Ojagbemi & Gureje, 2019 ; Olawa et al, 2019 ; Olawa & Idemudia, 2020 ; Taylor & Nguyen, 2020 ). The remaining eight studies used a modified version of the de Jong-Gierveld Loneliness Scale ( Han et al, 2017 ), a 20-point index measuring social contact ( Creecy et al, 1983 ), the Social Isolation component of a Patient-Reported Outcomes Measurement Information System ( Yoo-Jeong et al, 2020 ), single-item question, for example, “did you feel lonely for much of the day yesterday or in the past seven days?” ( Choi et al, 2021 ; Phaswana-Mafuya & Peltzer, 2017 ; Taylor et al, 2018 ; Victor et al, 2012 ), or two-item questions, for example, “are there times when you have a feeling of loneliness and what do you think needs to be done to reduce this loneliness?” ( Nzabona et al, 2016 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations